2011
DOI: 10.5558/tfc2011-025
|View full text |Cite
|
Sign up to set email alerts
|

Climate change adaptation and sustainable forest management: A proposed reflexive research agenda

Abstract: This article is a synthesis of the salient topics discussed in the Climate Change Adaptation and Sustainable Forest Management (SFM) Workshop, held at the University of British Columbia, February 14-16, 2011, and lays out a research agenda based on the recommendations for future research that emerged in the workshop. The proposed research agenda is framed using the theory of reflexive modernization to enable the forest research community to consider how different modes of knowledge production can support adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…However, Nilsson et al (2012) found that institutionalising of knowledge and knowledge exchange regarding climate change adaptation in Sweden was weak and that improved mechanisms are required for feedback from the local to the national level. Recent studies have described stronger relationships between scientific research and forest management to assess trade-offs and synergies, for participatory decision making and for shared learning Littell et al 2012;Klenk et al 2011).…”
Section: Policy Arrangements For Adaptationmentioning
confidence: 99%
“…However, Nilsson et al (2012) found that institutionalising of knowledge and knowledge exchange regarding climate change adaptation in Sweden was weak and that improved mechanisms are required for feedback from the local to the national level. Recent studies have described stronger relationships between scientific research and forest management to assess trade-offs and synergies, for participatory decision making and for shared learning Littell et al 2012;Klenk et al 2011).…”
Section: Policy Arrangements For Adaptationmentioning
confidence: 99%
“…They also provide a science-based rationale for forest management decisions [48] based on the adaptation approach to forest ecosystems [49]. Forest management adaptation strategies [50] aimed at sustainability must take into account a range of economic [51] and social aspects [52][53][54]. There are many uncertainties concerning the impact of climate change on European forests [6], so another goal of this study is to highlight the importance of the somewhat neglected biogeographical models, rooted in the concept of the forest vegetation zones.…”
Section: Introductionmentioning
confidence: 99%
“…Klenk et al (2011), for example, use the framework of reflexive modernization to highlight governance obstacles to achieving sustainable forest management goals. While some studies have explicitly recognized the need for a theoretical synthesis that addresses governance variables in natural resource and environmental studies without appealing to functionalist explanations of how these variables affect other system components, these remain few and far between.…”
Section: Discussionmentioning
confidence: 99%